Konsep Negara dalam Hukum Tata Negara Islam dan Relevansinya pada Negara Modern - Tasya Almutia Ramadani; Achmad Rafiu; Kurniati Kurniati (SPT. haria Journal and Education Center Publishing, 2026)
The state in Islamic constitutional law possesses a broader dimension compared to the general concept of the state, as it is not merely administrative but also encompasses moral, spiritual, and orientation-based aspects towards the common good (kemaslahatan umat). Although studies on the concept of the state in Islamic constitutional law have developed, most previous research has discussed specific aspects separately and has yet to comprehensively examine the relationship between the concept of the state in Islamic constitutional law and the dynamics of the modern state. This research aims to describe the nature of the state in Islamic constitutional law, analyze the opportunities and challenges of its implementation in modern states, and identify Islamic constitutional values that can be realized within a modern state. This is a library research study employing a normative-philosophical approach, utilizing primary sources such as classical and contemporary fiqh siyasah (Islamic political jurisprudence) texts as well as relevant and current scientific journals, which are analyzed in a descriptive-analytical manner. The results of the study indicate that the nature of the state in Islamic constitutional law is an institution that performs governmental functions while simultaneously actualizing the values of justice and public welfare based on maqasid al-sharia (the objectives of Islamic law). The implementation of Islamic constitutional law in modern states exists in a dialectical position between opportunities and challenges; its opportunities lie in the universality of its principles, which are in harmony with modern democracy, while its challenges include social change, the plurality of scholarly interpretations, and global human rights standards. Furthermore, the values of Islamic constitutional law that can be realized in a modern state include justice (al-'adl), consultation (syura), trust (amanah), public interest (maslahah), and equality (al-musawah).